2017
DOI: 10.1530/eje-16-0668
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric factors have significant influence on the outcome of the GHRH–arginine test: establishment of normative data for an automated immunoassay specifically measuring 22 kDa human growth hormone

Abstract: BMI and sex account for most of the variability of peak GH levels during GARG. Consequently, diagnostic accuracy of the GARG test is significantly improved by use of adjusted cutoffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
2
11
0
1
Order By: Relevance
“…In accordance with a recent study by Deutschbein et al [14] we found that the peak GH values in the GHRH + ARG test are clearly higher in healthy females than in males within the same BMI group. With the current BMI-related cut-off limits of AGHD, all female controls were classified as GH sufficient, whereas 22% (14/65) of the males were misclassified as insufficient.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with a recent study by Deutschbein et al [14] we found that the peak GH values in the GHRH + ARG test are clearly higher in healthy females than in males within the same BMI group. With the current BMI-related cut-off limits of AGHD, all female controls were classified as GH sufficient, whereas 22% (14/65) of the males were misclassified as insufficient.…”
Section: Discussionsupporting
confidence: 93%
“…The reliability and reproducibility of pharmacological stimulation tests in the diagnosis of GHD are still under discussion. Albeit findings have been somewhat controversial, age and gender obviously also affect the GH response in the GHRH + ARG test [6,8,[11][12][13][14]. Furthermore, there is a significant variation between GH results obtained by assays from different manufactures, which invalidates the use of common cut-off limits [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also provide further evidence that in healthy subjects, GH nadir concentrations as measured by a modern, widely available, automated GH assay which fulfills recent consensus criteria regarding calibration, specificity and sensitivity are much lower than the current cut-offs mentioned in guidelines for the diagnosis and follow-up of acromegaly (7). From studies on GH deficiency, it is known that BMI predicts GH response to GHRH arginine stimulation and that baseline GH tends to be lower in obese as compared to normal weight subjects (34,35,36,37). We could show that also the degree of suppression of GH during OGTT highly depends on BMI (Figs 3 and 5).…”
Section: Discussionmentioning
confidence: 95%
“…Results taken from the External Quality Assessment Scheme 4/2017 organized by Reference Institute for Bioanalytics (RfB, Bonn, Germany), one of the two German proficiency testing organizations. More results can be accessed at http://www.rfb.bio significantly lower GH concentrations at baseline and during many stimulation tests, but also exhibit more pronounced suppression of GH secretion during OGTT (26)(27)(28). Furthermore, factors such as stress, sleep, nutritional status, exercise and sex hormones influence GH secretion (…”
Section: Biological Variables In the Interpretation Of Measured Gh Comentioning
confidence: 99%